ANALISIS PENGEMBANGAN PARIWISATA BUDAYA KOTA TANJUNGPINANG MENGHADAPI KENDALA KETERBATASAN SUMBER DAYA MANUSIA - Ida Rahayu (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
The development of cultural tourism in Tanjungpinang City, particularly on Penyengat Island, faces significant structural challenges due to the limited quantity and quality of local human resources. This study aims to analyse the cultural tourism development strategy in Tanjungpinang City, focusing on addressing human resource constraints and identifying effective models for local community empowerment. This research utilises a qualitative descriptive case study approach. Primary data were collected through participatory observations and in-depth interviews with purposively selected key informants, including traditional leaders, government officials, and local tourism awareness groups. Data were analysed interactively using thematic coding and validated through source and method triangulation. The findings reveal a critical gap in local human resource competencies, specifically regarding digital marketing literacy, foreign language proficiency, and modern historical storytelling techniques. Furthermore, existing government training programs are predominantly top-down and lack continuous practical mentoring, while the current tourism workforce is dominated by an aging population, with extremely slow youth recruitment. In conclusion, overcoming these human resource barriers requires a structural paradigm shift from ceremonial training to sustainable vocational mentoring and business incubation. Empowering local institutions and actively involving the younger generation are essential to ensure Tanjungpinang's cultural heritage is managed professionally and sustainably.